ANALISIS KESENJANGAN PEMBIAYAAN PENDIDIKAN DI INDONESIA: STUDI LITERATUR TERHADAP PERBEDAAN AKSES DAN KUALITAS ANTARA SEKOLAH NEGERI DAN SWASTA DI DAERAH PERKOTAAN DAN PEDESAAN - Apriliansyah, Farhan; Ahmad, Masduki; Rochimah, Heni (STKIP Pesisir Selatan, 2025)
This study aims to identify and analyze the education financing gap in Indonesia, particularly between public and private schools, as well as between urban and rural areas. The objective is to examine how funding disparities affect the quality and accessibility of basic and secondary education services. A qualitative descriptive approach was employed through a literature review method. The analysis focused on identifying patterns of inequality in funding allocation and its implications for educational quality. The study reveals significant disparities in education funding. Public schools in urban areas benefit from more stable and substantial funding through the School Operational Assistance (BOS) program, whereas private schools in rural areas rely heavily on community contributions with limited purchasing power. These funding gaps directly impact the availability of learning facilities, teacher quality, and student academic outcomes, further exacerbating long-term social inequality. This study offers a comprehensive and up-to-date synthesis of the structural disparities in Indonesian education financing. Its novelty lies in the analytical integration of BOS data, student performance indices, cross-subsidy models between regions, and the strategic role of corporate social responsibility (CSR) in education—elements rarely examined collectively in previous literature.